Case 3801: Procheneosaurus Matthew, 1920 and Tetragonosaurus Parks, 1931 (Archosauria, Ornithischia): request to set aside Opinion 193 and remove Procheneosaurus from the Official List of Generic Names in Zoology, and Tetragonosaurus from the Official Index of Rejected and Invalid Generic Names in Zoology. - Demirjian, Vahe D (Bulletin of Zoological Nomenclature)
Noticed in BZN 76 (30 Aug 2019): 98.